PENGARUH COMPETITIVE PRICING DAN CUSTOMER PERCEIVED VALUE TERHADAP KEPUTUSAN MENJUAL SMARTPHONE INFINIX PADA GERAI PENJUALAN SMARTPHONE DI PONTIANAK DAN KUBU RAYA DENGAN BRAND IMAGE SEBAGAI VARIABEL PEMEDIASI - Georgerius Graceallah; Robert (MANAJEMEN DEWANTARA, 2025)
This research aims to examine the relationship between the competitive pricing variable and customer perceived value on the decision to sell Infinix smartphones at sales outlets in Pontianak City and Kubu Raya Regency. Additionally, this study also analyzes the role of brand image as a mediating variable in the relationship between independent variables (competitive pricing and customer perceived value) and the dependent variable (selling decision). This research uses a quantitative approach. All outlets selling Infinix brand smartphones in Pontianak City and Kubu Raya Regency constitute the population in this study. Census method was used in sampling where the entire population was included as part of the sample. sample size in this study was 63 smartphone outlets spread across various regions in Pontianak City and Kubu Raya Regency. The research results indicate that brand image has a positive and significant effect on selling decisions, competitive pricing and customer perceived value have a positive and significant effect on brand image, competitive pricing and customer perceived value do not have a significant effect on selling decisions, competitive pricing and customer perceived value has a significant indirect effect on selling decisions through brand image.